2012
DOI: 10.4028/www.scientific.net/amr.446-449.151
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Finite Element Analysis of Diamond Bird-Beak TX-Joints

Abstract: Abstract. The diamond bird-beak TX-joint is a novel configuration for tubular structures and there are few correlated papers for it. Non-linear FE analysis is carried out on axially loaded TX-joints in order to study the local static behavior of this type of joint. The individual influence of the following geometric parameters on the joint capacity, section width ratio β of brace to chord members, section width to wall thickness ratio 2γ of chord member, and wall thickness ratio τ of brace to chord members is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Davies et al [10] focused on the effect of purlin loads on the capacity of overlapped diamond bird-beak K-joints. Zhu et al [11] and Liu et al [12] conducted FE analysis to estimate the ultimate capacities of axially loaded diamond bird-beak TX-and XX-joints. FE analysis was carried out by Peña et al [13] to study the ultimate load capacity of diamond bird-beak X-joints subjected to axial forces.…”
Section: Introductionmentioning
confidence: 99%
“…Davies et al [10] focused on the effect of purlin loads on the capacity of overlapped diamond bird-beak K-joints. Zhu et al [11] and Liu et al [12] conducted FE analysis to estimate the ultimate capacities of axially loaded diamond bird-beak TX-and XX-joints. FE analysis was carried out by Peña et al [13] to study the ultimate load capacity of diamond bird-beak X-joints subjected to axial forces.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous efforts including Ono et al [1][2][3], Ishida et al [4], Davies et al [5], Owen et al [6,8], Owen and Kelly [7], Chtistitas [9], Lei [10], Zhu and Liu [11] have been devoted to the ultimate resistance of bird-beak joints under static loads, and it shows that the ultimate strengths of bird-beak joints are obviously higher than those of conventional joints with the same non-dimensional parameters. The seismic resistance of bird-beak joints was also studied by Hall and Owen [12], where both conventional and diamond bird-beak X-joints were tested under inelastic cyclic loading, and better performance were observed for new configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Christitsas [9] and Lei [10] conducted experiments and a parametric FEM analysis of square bird-beak X-joints subject to in-plane bending and proposed formulas for design resistance as a result. Zhu and Liu [11] studied the non-linear behavior of axially loaded diamond bird-beak XT-joints using a finite element method. The studies indicated that the ultimate strengths of bird-beak joints were higher than those of conventional joints with the same non-dimensional parameters.…”
Section: Introductionmentioning
confidence: 99%